Structural design and testing of material optimized ribbed RC slabs with 3D printed formwork - Huber, Tobias; Burger, Joris; Mata‐Falcón, Jaime; Kaufmann, Walter (Structural concrete : journal of the FIB, 2023)
Most of the concrete volume in multistorey buildings is cast in solid slabs, which are frequently flat slabs supported on columns. By using two‐way spanning ribbed slabs, concrete consumption could be significantly reduced. However, due to the high costs associated with formwork, such a complex rib configuration is rarely used nowadays. With the advent of technologies for automated formwork fabrication, the material‐saving potential inherent in this structural system could again be exploited. This paper investigates the feasibility of material‐efficient ribbed concrete slabs on a building scale using conventional concrete and steel reinforcing bars cast inside a three‐dimensional‐printed plastic‐based formwork. To that end, the code‐compliant design of ribbed slabs is first discussed, followed by the introduction of a concept for an automated design‐to‐production workflow. The sustainability of this slab system is compared to a solution using conventional formwork in a case study consisting of a multibay office building with slabs spanning 8 m in both directions, revealing that ribbed slabs use 40% less concrete than solid slabs. Several representative structural elements of the case study (ribs, slab‐column transition) were produced at full‐scale and tested until failure to investigate the feasibility of production and structural performance. Three T‐beams with various rib shapes (straight, kinked with diaphragms, curved) were tested in a three‐point bending configuration, showing a ductile behavior with longitudinal reinforcement yielding and indicating the relevance of torsional effects in curved ribs. Punching tests on two slab‐column connections (ribbed, solid) revealed that the optimized ribbed slab could prevent brittle punching failures and achieve an ultimate load 105% higher than the solid reference slab. All specimens' load‐bearing behavior could be predicted using established design formulas, showing the feasibility of producing code‐compliant ribbed slabs with the applied technology.